Vehicle Stability Control Strategy Based on Active Torque Distribution and Differential Braking - Siqi Zhang; Tianxia Zhang; Shuwen Zhou (2009 International Conference on Measuring Technology and Mechatronics Automation, 2009)
The paper presents a vehicle yaw stability control strategy devoted to prevent vehicles from spinning and drifting out. The yaw stability control system is integrated with active torque distribution and differential braking system. Active torque distribution systems utilize active differentials to independently control the drive torque distributed to each drive wheel and thus provide active control of both traction and yaw moment. However, if the coefficient of road friction were small or if the vehicle speed were too high, active torque distribution system may not afford adequate yaw moment to response the driver needs. With this improved integrated control system, the vehicle can afford nice manoeuvrability and stability.